Upaya Satuan PAUD untuk Mengoptimalkan Kreativitas Anak Usia Dini dalam Kegiatan Menggambar Bebas - Felicia Yorenda Putri; Ratih Kusumawardani; Dian Surya Aprilyanti (Darul Yasin Al Sys, 2026)
Creativity is one of the important aspects of early childhood development that needs to be fostered through learning activities that provide space for children to express themselves. However, in practice, art activities in Early Childhood Education (ECE) institutions often remain structured and have not fully provided children with the freedom to develop their imagination. This study aims to describe the efforts of an ECE institution in optimizing early childhood creativity through free drawing activities. This study employed a qualitative approach with a descriptive design. The research subjects consisted of the principal, teachers, and children at TK Kemala Bhayangkari 05 Serang City. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that free drawing activities were carried out regularly as part of journal activities in the classroom by providing various drawing media, such as colored pencils, crayons, markers, watercolor paints, and acrylic paints. The teacher acted as a facilitator who created a safe, comfortable learning atmosphere and did not limit children’s ideas, so that children could express their imagination and feelings freely. This activity proved to be able to enhance children’s creativity, as indicated by their courage in expressing ideas, the variety of drawing forms, and their ability to explain their work. Thus, free drawing activities supported by adequate media, a conducive learning environment, and the teacher’s facilitative role can optimize the development of early childhood creativity. The implications of this study emphasize the importance of implementing art activities that highlight children’s creative process in ECE learning.